Analysis of Legal Protection For Household Workers Without Employment Contracts - Farrel Farandy; Wardani Rizkianti (Green Publisher Indonesia, 2025)
This study analyzes the urgency of legal protection for Domestic Workers (PRT) in Indonesia. The background is the significant increase in the number of domestic workers from 2015 to 2022. Despite their vital role, they are still vulnerable to violence and exploitation due to the lack of formal recognition and employment contracts. The main problem stems from the exclusion of domestic workers from the Manpower Law No. 13 of 2003 and the stalled ratification of the PPRT Bill since 2004. Using a normative juridical legal analysis method, this study concludes that the ratification of the PPRT Bill is a top priority to provide a legal basis, rights standards, and effective enforcement mechanisms for domestic workers' protection. It is also recommended that a comprehensive and transparent employment contract be formulated, supported by preventive and repressive efforts through public education, increased legal awareness, and strict supervision by the government and community participation, in order to realize justice and the welfare of domestic workers in Indonesia.